Total Neoadjuvant Therapy (TNT) versus Standard Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer: A Systematic Review and Meta‐Analysis - Liu, Shuang; Jiang, Ting; Xiao, Lin; Yang, Shanfei; Liu, Qing; Gao, Yuanhong; Chen, Gong; Xiao, Weiwei (The oncologist (Dayton, Ohio), 2021)
Background Total neoadjuvant therapy (TNT) is a novel approach for locally advanced rectal cancer (LARC), which attempts to deliver both systemic chemotherapy and neoadjuvant chemoradiotherapy prior to surgery. However, its efficacy and safety remain controversial in randomized controlled trials (RCTs). We conducted this meta‐analysis to assess such concerns. Materials and Methods Head‐to‐head phase II/III RCTs were searched in Embase, PubMed, Web of Science, and the Cochrane Library, as well as other sources. The primary endpoint was pathologic complete response (pCR). Secondary endpoints were disease‐free survival (DFS), overall survival (OS), local recurrence‐free survival, distant metastasis‐free survival, and the R0 resection rate. Results Eight phase II/III RCTs involving 2,196 patients with LARC were assessed. The primary analysis demonstrated a statistically significant improvement in the pCR rate for TNT treatment (odds ratio, 1.77; 95% confidence interval [CI], 1.28–2.45; p = .0005). TNT treatment also showed improvements in DFS and OS outcomes compared with standard chemoradiotherapy (hazard ratio [HR], 0.83; 95% CI, 0.72–0.96; p = .03 and HR, 0.88; 95% CI, 0.74–1.05; p = .15). In addition, TNT treatment showed significant efficacy in reducing the risk of distant metastasis (HR, 0.81; 95% CI, 0.68–0.95; p = .012). Conclusion The overall pCR rate may be improved with TNT compared with standard treatment. The TNT strategy may also improve DFS and OS and reduce the risk of distant metastasis. Implications for Practice Locally advanced rectal cancer (LARC) is a relatively common disease, with a poor prognosis because of its high metastatic potential. The role of total neoadjuvant therapy (TNT) has always been controversial. This meta‐analysis found that TNT in LARC is associated with a significant improvement in overall pathologic complete response rate, disease‐free survival, overall survival, and distant metastasis‐free survival compared with standard treatment. TNT is a promising strategy for LARC, especially for patients who have little desire for surgery. Total neoadjuvant therapy (TNT) is a novel therapeutic approach for locally advanced rectal cancer that delivers both systemic chemotherapy and neoadjuvant chemoradiotherapy before surgery; however, this approach remains controversial. This article reports the results of a meta‐analysis comparing TNT with standard chemotherapy.